Serological and cellular inflammatory signatures in end‐stage kidney disease and latent tuberculosis. Issue 11 (5th November 2021) - McLean, Milla R; Wragg, Kathleen M; Lopez, Ester; Kiazyk, Sandra A; Ball, Terry Blake; Bueti, Joe; Kent, Stephen J; Juno, Jennifer A; Chung, Amy W
Abstract: Objectives: Tuberculosis comorbidity with chronic diseases including diabetes, HIV and chronic kidney disease is of rising concern. In particular, latent tuberculosis infection (LTBI) comorbidity with end‐stage kidney disease (ESKD) is associated with up to 52.5‐fold increased risk of TB reactivation to active tuberculosis infection (ATBI). The immunological mechanisms driving this significant rise in TB reactivation are poorly understood. To contribute to this understanding, we performed a comprehensive assessment of soluble and cellular immune features amongst a unique cohort of patients comorbid with ESKD and LTBI. Methods: We assessed the plasma and cellular immune profiles from patients with and without ESKD and/or LTBI ( N  = 40). We characterised antibody glycosylation, serum complement and cytokine levels. We also assessed classical and non‐classical monocytes and T cells with flow cytometry. Using a systems‐based approach, we identified key immunological features that discriminate between the different disease states. Results: Individuals with ESKD exhibited a highly inflammatory plasma profile and an activated cellular state compared with those without ESKD, including higher levels of inflammatory antibody Fc glycosylation structures and activated CX3CR1 + monocytes that correlate with increased inflammatory plasma cytokines. Similar elevated inflammatory signatures were also observed in ESKD + /LTBI + compared with ESKD − /LTBI +, suggesting that ESKD induces an overwhelming inflammatory immune state. In contrast, no significant inflammatory differences were observed when comparing LTBI + and LTBI − individuals. Conclusion: Our study highlights the highly inflammatory state induced by ESKD. We hypothesise that this inflammatory state could contribute to the increased risk of TB reactivation in ESKD patients. Abstract : End‐stage kidney disease (ESKD), regardless of aetiology, shares a common, highly inflammatory course promoting monocyte activation, leukocyte chemoattraction, and generalised inflammation. With substantial rates of TB reactivation in this patient group and mechanistic uncertainty, our study assesses plasma and cellular immune profiles from ESKD patients with and without latent tuberculosis infection (LTBI). We learn how ESKD + /LTBI + co‐infection remains a highly inflammatory state compared to ESKD − /LTBI + and find unique inflammatory signatures driven by the presence of ESKD.